2010
DOI: 10.1111/j.1365-277x.2009.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an electromagnetic imaging system to facilitate nasogastric and post‐pyloric feeding tube placement in patients with and without critical illness

Abstract: This system confers advantages, particularly in terms of post-pyloric tube placement, even at this early stage of implementation. A reduction in clinical risk and cost avoidance related to X-ray exposure, the need for endoscopic tube placement and parenteral nutrition have been achieved. The implementation of this system should be considered in other centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 11 publications
1
25
0
5
Order By: Relevance
“…Various combinations of key words used in the search included electromagnetic phenomena, enteral nutrition, instrumentation, gastrointestinal, point-ofcare testing, pneumothorax, and Cortrak. Fifteen published studies 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] were found that evaluated the effectiveness of an ETP device in determining tube location. These studies were reviewed for any reference to detection of bronchopulmonary placements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various combinations of key words used in the search included electromagnetic phenomena, enteral nutrition, instrumentation, gastrointestinal, point-ofcare testing, pneumothorax, and Cortrak. Fifteen published studies 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] were found that evaluated the effectiveness of an ETP device in determining tube location. These studies were reviewed for any reference to detection of bronchopulmonary placements.…”
Section: Methodsmentioning
confidence: 99%
“…3 Researchers in multiple studies have evaluated the effectiveness of an electromagnetic tube placement (ETP) device in distinguishing between tube placement in the stomach and in the small bowel. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, fewer studies have involved evaluation of the effectiveness of an ETP device in detecting bronchopulmonary placements. 1,6,11,12,14,16 Purpose This study had 2 purposes: 1.…”
mentioning
confidence: 99%
“…This method has been used with success in patients with previously difficult access 60 and is cost-effective, reducing X-ray exposure and time to initiation of enteral feeding.…”
Section: -59mentioning
confidence: 99%
“…The implementation of a new strategy for confirming correct tube placement requires good nursing education, compliance and multidisciplinary team work. Windle et al [88] used an electromagnetic imaging system in order to assess the correct placement of NGTs and showed that this method has some advantages, especially in confirming the post-pyloric placement of an NGT even at the early stage of implementation.…”
Section: Assessment Of Correct Placementmentioning
confidence: 99%